Encountering education in the rural: migrant women's perspectives. Issue 3 (4th May 2017) - Mayes, Robyn; McAreavey, Ruth
ABSTRACT: This paper explores migrant women's encounters with formal and informal education in what can be termed new immigration rural destinations. We ask to what extent educational opportunities are realized in these new destinations. We show that education aspirations may be jeopardized because of the desire to achieve economic goals and thus require remedial action. Specifically, we refer to qualitative data collected in rural (and remote) Boddington in Western Australia, and rural Armagh in Northern Ireland. The paper engages with two interrelated dimensions of this migrant/migration experience. English is not a first language for our participants and we first examine the provision and consumption of informal English Language classes. In doing so, we demonstrate the complex social and cultural dimensions of community-based English language instruction. Second, we attend to migrant mothers' perceptions of and responses to children's formal education. We highlight transnational senses of, and tensions around, 'local/rural' pedagogies and resultant migrant strategies.